2020
DOI: 10.3389/fpsyg.2020.01632
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Psychotic-Like Symptoms Affect Cognitive Abilities but Not Motivation in a Foraging Task

Abstract: Background and Objective: Goal-directed behavior is a central feature of human functioning. It requires goal appraisal and implicit cost-benefit analyses, i.e., how much effort to invest in the pursuit of a certain goal, against its value and a confidence judgment regarding the chance of attainment. Persons with severe mental illness such as psychosis often struggle with reaching goals. Cognitive deficits, positive symptoms restricting balanced judgment, and negative symptoms such as anhedonia and avolition ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
(90 reference statements)
2
6
0
Order By: Relevance
“…It has been suggested that implicit metacognition relies on a different cognitive system than explicit metacognition and is only minimally dependent on working memory [ 57 ]. These findings are also in line with recent reports of intact implicit metacognition in SCZ [ 44 ] and metacognitive efficiency in first episode psychosis [ 58 ]. Interestingly, metamemory was negatively related to estimated volatility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that implicit metacognition relies on a different cognitive system than explicit metacognition and is only minimally dependent on working memory [ 57 ]. These findings are also in line with recent reports of intact implicit metacognition in SCZ [ 44 ] and metacognitive efficiency in first episode psychosis [ 58 ]. Interestingly, metamemory was negatively related to estimated volatility.…”
Section: Discussionsupporting
confidence: 92%
“…A visual working memory task developed based on previously published paradigms [ 42 , 43 ] and a variant of the paradigm used by ten Velden Hegelstad and colleagues [ 44 ], was administered to measure both visual working memory and implicit metamemory as a proxy for metacognition. An implicit measure was chosen since uncertainty may be encoded without awareness and not accessible to explicit reports [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that implicit metacognition relies on a different cognitive system than explicit metacognition and is only minimally dependent on working memory [57]. These findings are also in line with recent reports of intact implicit metacognition in SCZ [44] and metacognitive efficiency in first episode psychosis [58]. Interestingly, metamemory was negatively related to estimated volatility.…”
Section: Plos Onesupporting
confidence: 85%
“…Visual working memory task. A visual working memory task developed based on previously published paradigms [42,43] and a variant of the paradigm used by ten Velden Hegelstad and colleagues [44], was administered to measure both visual working memory and implicit metamemory as a proxy for metacognition. An implicit measure was chosen since uncertainty may be encoded without awareness and not accessible to explicit reports [45].…”
Section: Plos Onementioning
confidence: 99%
“…Positive symptoms of psychosis (e.g., paranormal beliefs) were measured using the 20 frequency items in the positive subscale of the Community Assessment of Psychic Experiences scale (CAPEp: [ 62 ]), which can be divided into five subscales [ 65 ]. Similar to the AQ-short, the CAPEp has been used to meausure traits in non-clinical samples [ 66 , 67 ]. We added three control questions reflecting common misconceptions about psychosis [ 68 ], such as whether one believes in kidnappings by aliens.…”
Section: Methodsmentioning
confidence: 99%